Melanogenesis Inhibitors - Sulekha Kumari; Steven Tien Guan Thng; Navin Kumar Verma; Hemant K. Gautam (Medical Journals Sweden, 2018)
Abnormally high production of melanin or melanogenesis in skin melanocytes results in hyperpigmentation disorders, such as melasma, senile lentigines or freckles. These hyperpigmentary skin disorders can significantly impact an individual's appearance, and may cause emotional and psychological distress and reduced quality of life. A large number of melanogenesis inhibitors have been developed, but most have unwanted side-effects. Further research is needed to better understand the mechanisms of hyperpigmentary skin disorders and to develop potent and safe inhibitors of melanogenesis. This review summarizes the current understanding of melanogenesis regulatory pathways, the potential involvement of the immune system, various drugs in current use, and emerging treatment strategies to suppress melanogenesis.